Migration and Socio-Cultural Adaptation of Bugis Ethnic Migrants in Palu City - Syufri, Syufri; Khairil, Muhammad; Muhammad, Hasan; Amir, Andi Mascunra (Green Publisher Indonesia, 2023)
The aims of this study were 1) to find out about the migration process of the Bugis ethnic group to Palu City, to explain the driving factors in the area of ​​origin of South Sulawesi, the pull factors in the destination area of ​​Palu City as well as the inhibiting factors and barriers to migrating to Palu City. 2) Knowing about social interactions and socio-cultural adaptations of the Bugis ethnic in Palu City. The method used is a qualitative approach involving 8 informants. The results showed that: Migration of the Bugis Ethnic to Palu City was motivated by economic factors due to limited job opportunities and increasingly competitive life along with population growth in the area of ​​origin of South Sulawesi. The factor of